Greenland, stream and valley at Kjerulf Fjord - Boyd, Louise Arner, 1887-1972 (1931)
August 1, 1931. Kjerulfs [Kjerulf] Fjord. Extreme inner end. In background on left; eastern side of Left Valley. This is formed by range of mountains extending south on eastern side of Kjerulfs [Kjerulf] Fjord. In extreme background; glaciers on mountain range just south of L.A.B.'s Scoop Mt. [Mountain] In foreground waters (at stream mouths) of both Right and Left Valleys. Photo taken looking S.S.E. from floor of Main Valley at its junction with Left and Right Valleys.